キョウヤク テン ニ オケル チジキ ヘンドウ ノ トウケイ テキ トクセイ - 橋本, 久美子; ハシモト, クミコ; 佐藤, 夏雄; サトウ, ナツオ; 楠瀬, 昌彦; クスノセ, マサヒコ; Hashimoto, Kumiko; Sato, Natsuo; Kusunose, Masahiko (1993)
P(論文) 昭和基地-アエデ(アイスランド)の地磁気共役点において同時に観測されたfluxgate磁力計による地磁気のH(南北)成分を用いて, オーロラジェット電流の東西成分の共役性について統計的な解析を行った。本研究では各月ごとに, 地磁気の静穏時の値からの変差を地磁気変動量と定義している。1989年9月-1990年9月の13カ月間のデータを用いて, 両観測点における地磁気変動量の共役性の日変化, 季節変化などの特性が得られた。解析の結果, 午後から夜にかけてみられるH成分の北向きの変動(東向きオーロラジェット電流)は, 夏半球側が冬半球側より3~5倍ほど大きく, アエデが夏季の1800 UT頃に最も差が大きくなる。また, 2月と10月に変動量は等しくなる。一方, 夜中から朝にかけてみられるH成分の南向きの変動(西向きオーロラジェット電流)は静穏時には夏半球側が冬半球側より1.5~3倍ほど大きく, 4月と8月に変動量が等しくなる。共役点におけるこれらの非共役な現象は, 両観測点の地理座標の差異による日照条件の違いとよく一致する。また, 磁気活動度が高くなるとともに, 北向きの変動の場合も南向きの変動の場合もともに, 昭和基地の地磁気変動量が相対的にアエデより大きくなる傾向がある。このことは両観測点におけるオーロラ粒子の降り込みによる電離層の電離効率の違いと同じ傾向にある。 The diurnal and seasonal dependence of the conjugacy of geomagnetic variations associated with the auroral electrojet is investigated and their dependence on ionospheric conductivity (due to solar EUV and auroral particle precipitations) is examined. We analyze the fluxgate magnetometer data from two magnetic conjugate stations at Syowa in Antarctica and at Aedey in Iceland, during the period from September 1989 to September 1990. Here, a magnitude of geomagnetic variation is defined as a deviation from quiet time geomagnetic elements for each month. We further examined a ratio of the magnitudes of the geomagnetic variations between two stations (ΔHSYOWA/ΔHAEDEY). Principal characteristics of the magnitude ratio between two conjugate observatories include the following : When the sense of magnetic variations of H component is positive (northward), the magnitude in the summer hemisphere is about three times larger than that in the winter hemisphere during 1300-2000 UT, and the magnitude ratio becomes largest around 1800 UT in the northern summer. Almost the same magnitude of geomagnetic variations at the two observatories appeared at around 1800 UT in February and October. On the other hand, for negative variation (southward), a similar seasonal change can be seen only under low magnetic activity conditions. The magnitude ratio for the negative variation is always smaller than that for the positive one. The ratios are equal ...